Development of mango cider - Lopez, Jovita Carla H.; Rillo, Belen O. (1984.)
The major objective of this study is to produce mango cider utilizing mango pomace, a waste material from the production of mango juice. The best proportion of mango pomace to water to prepare the raw material was determined in Phase !. Phase II involved the determination of the best clarifying method of the mango juice and Phase III was the determination of a satisfactory yeast starter for fermentation. Results obtained showed that a proportion of 1:2 mango pomace to water was the best starting base for fermentation. Among the clarification methods investigated, i.e., filtration, gelatin, bentonita and heating, filtration obtained the best results for color (golden yellow) and was found to be slight to moderately clear which was significant at 5% level. Objective tests on the physico-chemical properties of the clarified samples showed no change for pH and percent soluble solids for all samples except for heat treated sample and a decrease in percent titrable acidity. Bentonite treated sample resulted in an extremely clear product with color evaluation of off-color to white. The yeast starter S. cerevisiae produced cider with higher alcohol content than that produced by S. cerevisiae var. ellipsoideus. However, the latter was "slightly" to "moderately liked" while cider produced by S. cerevisiae was "neither liked nor disliked" to "liked slightly."
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit wines; Mango